Growth, yield and isotope composition of carbon and nitrogen in rice as influenced by different potassium fertilizer sources in selected granary areas - Mohd Anuar, Nuraini Shafinaz (2023)
Rice (Oryza sativa L.) plays a vital role in ensuring food security in Malaysia, particularly in the granary areas such as MADA and KADA. These regions serve as significant riceproducing areas, contributing substantially to the nation's rice production. The key role of potassium (K) fertilization is crucial in rice cultivation, impacting various physiological processes and contributing significantly to the quality and yield of rice crops in granary areas. Exploring alternative potassium sources, such as polyhalite, holds potential for improving Malaysian agriculture. The examination of δ13C and δ15N provides significant insights into the acquisition of resources and interactions among plants. This is because the natural abundance of carbon-13 and nitrogen-15 in plants reflects the isotopic composition of their carbon and nitrogen sources and plays a crucial role in advancing our understanding of various ecological and biological processes. However, the extent to which the intake of K affects the isotopic variance in rice has not been well studied. Therefore, this study aims to comprehensively investigate the effects of potassium (K) fertilizers on rice plant physiological parameters and yield performance. The primary objectives include assessing the impact of K fertilizer sources on stable carbon and nitrogen isotope values (specifically δ13C and δ15N) in rice tissues, examining the influence of K fertilizers on rice photosynthesis, and investigating the effects of K fertilizers on rice yield. Field tests in KADA and MADA regions and a rain shelter experiment were conducted to achieve these goals, providing valuable insights into agriculture and crop management. Rice plants were cultivated in the field and under a rain shelter with five treatments, which are T1 (no-K), T2 (Muriate of Potash), T3 (Sulphate of Potash), T4 (Polyhalite), and T5 (conventional fertilizer). The fertilizers were applied 3, 15, 55, and 75 days after planting (DAP). Leaf photosynthesis and stomata conductance measurements were taken at 85 DAP and dried and reserved for carbon and nitrogen isotope analyses. Meanwhile, the rice yield was determined at 110 DAP during harvest. In this study, the rain shelter trials highlighted the positive influence of K fertilizers on rice yield, with Polyhalite consistently providing the highest yields under controlled conditions with 490.4 g/pot for KADA and 489.60 g/pot for MADA soils compared to other treatments. Overall, adding K fertilizer proved beneficial for rice plant health, tiller productivity, and grain yield, emphasizing the importance of potassium fertilization in enhancing overall rice productivity. While soil type does not significantly impact rice yield, MADA soil demonstrates a more conducive environment for photosynthesis and improved efficiency in water and nutrient absorption with a mean of 52.77 μmol CO2 m-2 s-1 for rate of photosynthesis and 1.88 mmol m-2 s-1 for stomata conductance. Polyhalite, a potassium source, significantly boosted photosynthetic rates and stomata conductance. The findings also indicated that K fertilizer application could influence δ15N in plants, with variations observed in different treatments and environmental conditions. The comprehensive analysis of correlation coefficients highlighted complex interactions between rice yield, rate of photosynthesis, stomata conductance, and isotopic values, providing valuable insights for crop management and sustainable agricultural practices. In conclusion, the study emphasized the importance of K in enhancing rice productivity, influencing plant physiology, and contributing to the intricate dynamics of carbon and nitrogen isotopic signatures in plants.